2014
DOI: 10.1007/s11051-014-2650-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and luminescent properties of ultrasmall colloidal CdS nanoparticles stabilized by Cd(II) complexes with ammonia and mercaptoacetate

Abstract: The synthesis of stable water-soluble ultrasmall 1.8 nm CdS nanoparticles co-stabilized with Cd(II) complexes with NH 3 and mercaptoacetate ions is reported. The CdS nanoparticles emit broadband photoluminescence with a peak at 2.3 eV and a quantum yield of up to 15 %. The photoluminescence decay is strongly non-exponential and characterized by an average radiative life-time increasing from 46 to 105 ns as the emission quantum energy decreases from 2.9 to 1.8 eV. The photoluminescence intensity and life-time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…As discussed above, the temperature dependences of the intensity and spectral parameters of aqueous AIS (and AIS/ZnS) NCs stabilized by GSH complexes are very similar to those of aqueous CdS NCs stabilized both by Cd(II)‐PEI complexes and Cd(II)‐NH 3 ‐MA complexes . All three types of NCs indeed show linear Arrhenius‐like dependences of the PL intensity on temperature (SI, Figure S4) with apparent PL quenching activation energies of 2 nm CdS‐PEI and 2 nm CdS‐NH 3 ‐MA NCs estimated to be (310±10) meV and (250±10) meV, respectively (Figure d, blue bars).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…As discussed above, the temperature dependences of the intensity and spectral parameters of aqueous AIS (and AIS/ZnS) NCs stabilized by GSH complexes are very similar to those of aqueous CdS NCs stabilized both by Cd(II)‐PEI complexes and Cd(II)‐NH 3 ‐MA complexes . All three types of NCs indeed show linear Arrhenius‐like dependences of the PL intensity on temperature (SI, Figure S4) with apparent PL quenching activation energies of 2 nm CdS‐PEI and 2 nm CdS‐NH 3 ‐MA NCs estimated to be (310±10) meV and (250±10) meV, respectively (Figure d, blue bars).…”
Section: Resultssupporting
confidence: 54%
“…Earlier we reported on the synthesis and PL properties of ultra‐small (the size d <2 nm) CdS NCs stabilized by Cd(II) complexes with PEI or by a combination of MA and ammonia . Both types of CdS NCs revealed very similar reversible variations of the PL intensity when heated up and cooled down in aqueous colloidal solutions (see examples in SI, Figure S3).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The synthesis of surface-modified CdS QDs, CdS-(I) and CdS-(II) dyad assemblies is described as follows. In order to engineer photochrome-chromophore dyad, the CdS QDs were synthesized by performing slight modifications to the procedure given by Raevskaya et al [14]. For this purpose, ambient conditions were maintained, i.e.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Taking into account the complexity of such synthesis alternative methods of formation of luminescent semiconductor metal-chalcogenide NPs directly in water were in the focus of interest for the last several years [5,12]. It was found that the water-soluble cadmium chalcogenide NPs featuring reasonably high PL QY (10-20%) can be produced directly in the presence of a number of polymer stabilizers [12] such as glycodendrimers, block-copolymers [5,12], polyethyleneimine [17] as well as combinations of molecular species, for example, ammonia and mercaptoacetate complexes with Cd(II) [18].…”
Section: Introductionmentioning
confidence: 99%